A pilot-scale three-dimensional electrochemical reactor combined with anaerobic-anoxic-oxic system for advanced treatment of coking wastewater. (15th March 2020) - Liu, Yang; Wu, Zhen-yu; Peng, Pin; Xie, Hong-bo; Li, Xiu-yan; Xu, Juan; Li, Wei-hua
Abstract: Coking wastewater is highly concentrated and extremely toxic, greatly challenging the treatment technologies. Conventional biological technology such as anaerobic-anoxic-oxic (A 2 O) system is inefficient, since various biological reactions are inhibited by toxicants in coking wastewater. In this work, a pilot-scale three-dimensional electrochemical reactor (3DER) is integrated into the A 2 O system as a pretreatment unit to improve the treatment efficiency of coking wastewater. The results indicate that 3DER pretreatment increased the biodegradability of coking wastewater, promoting the degradation of coking wastewater in A 2 O system. The integrated 3DER-A 2 O system can remove 94.4% of COD and 76.2% of TN from coking wastewater, and the energy consumption was only 0.22 kWh/kg COD and 4.69 kWh/kg TN. The components of coking wastewater were significantly simplified and the acute toxicity was reduced from 99% to 12% after the treatment. The integrated 3DER-A 2 O system provides a new solution for coking wastewater treatment, showing a promising application potential. Graphical abstract: Image 100603 Highlights: A pilot-scale 3DER is integrated into an A 2 O system for coking wastewater treatment. 94.4% of COD and 76.2% of TN are removed by the integrated system. 3DER pretreatment increases the biodegradability of coking wastewater. Coking wastewater is purified and detoxified by the integrated system.